A decade of professionalisation in physical education and sports science in Africa (1994-2004) - Amusa, L. O.; Toriola, A. L. (Journal of Human Movement Studies, 2005)
The old adage "with time comes change" is certainly true with respect to developments in Africa in physical education (PE) and Sports science (SS) in the last decade. The fields have emerged from mere pockets of isolated practices to a more cohesive global acadeniically respectable profession. Of particular interest is the emergence and growth of sub-regional and continent-wide Professional bodies with direct or indirect association with govemment departments of education. health. sports and private organisations. This article reviews Professional milestones in the evolution of PE and SS in Africa and analyses prospects for future development.